SOSIALISASI PENTINGNYA KLASIFIKASI KODEFIKASI PENYAKIT KASUS BALITA DALAM MENUNJANG KLAIM ASURANSI JKN PADA MASA DIGITALISASI REKAM MEDIS ELEKTRONIK - Putra Pradnyantara, I Gusti Agung Ngurah; Ni Ketut Ayu Mirayanti; Luh Nova Dilisca, Ni; made wahyu aditya (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
SatuSehat is a national integrated health data exchange platform, currently Satu Sehat will be developed to play an active role in the digitalization of health data, the health service process will be carried out through the Satu Sehat platform, the codification classification is very useful for health workers because it is the main benchmark in health financing. Health services are inseparable from health financing, especially in the implementation of JKN, so health workers are required to maximize services, especially to avoid errors in the claim process, socialization regarding the classification of disease codification based on ICD 10 is very necessary in order to provide an overview of the claim process in the health service provider environment, the target of this socialization is SMK Kesehatan students. The method used is to socialize the introduction of disease codification classification for 45 minutes and examples of its implementation, the results of this community service found that students had never received basic knowledge about the Classification and codification of diseases, students were enthusiastic and followed all the presentations given, there was a significant increase in student knowledge about the claim process.